IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH PADA SEKOLAH LUAR BIASA (SLB) YPAC MEDAN - Indra Muda (PERSPEKTIF, 2016)
For education achievement purpose both regionally and nationally are now developed at school-based management, the system is expected to foster the ability of schools to manage the continuity of teaching and learning process. to obtain the data in this research conducted interviews, observation and documentation study of objects of research. According to research, the implementation of school-based management in SLB - Medan YPAC stakeholders are involved, the council consists of teachers, school committee, the foundation is guided by the educational curriculum. In the determination of policies such as the determination of hours of study, days off or to take the kids study tour, conducted by the school committee meeting. If the stakeholders agree with the policy set has just been implemented. Similarly, the maintenance of cleanliness and neatness of children enter school and after school, always communicated with the school committee so that the patterneducate and nurture children do together. Conclusions in the research that is, the preparation of school-based management planning on SLB - YPAC Medan involving all stakeholders such as councils of teachers, administrators YPAC, school committees and agencies. Inhibiting factor in planning school-based management of most of the school committee is not familiar with school-based management.